Group buy eCommerce application - Ong, Kean Huan (2022)

(untitled)
The application developed for this project is a mobile application related with group buy. Although online shopping is a common scenario nowadays, the innovation of group buy is still under development phase in Malaysia. Based on the analysis, some of the eCommerce applications such as Pinduoduo and Taobao do not provide rating function in product review. These applications are using word rating instead of star rating which might not be effective to the buyers. Furthermore, the current group buy applications are still lack of communication channel among the consumers. Hence, one of the objectives of the project is to implement the es. This may help the buyers to understand about the particular product based on comment and review before purchase. The second objective of the project is to develop a group feature in the application to establish a communication channel among users. This can help the buyers to gather their purchasing power easily. Review and analysis on similar websites such as Taobao, Alibaba, Amazon, Pinduoduo and Qoo10 are conducted to ensure required features and improvement are determined for the application before implementation phase. Then, the design, layout and functions of the application are designed before development. The user roles existing in the application are buyer, seller, and customer service. The application allows buyers to create group buy and join group buy. It also supports single purchase and add products to cart. Other than that, the buyers and sellers are able to manage their orders and provide rating. The general functions such as login, registration, payment, update profile and manage products are also available in the application. The methodology applied in the project is waterfall approach which involve planning, analysis, design, implementation, testing and evaluation, and documentation. Moreover, the technologies used in the project are Java, JavaScript, Android Studio, Git, Heroku, Firebase and Node.js to build the application. The Node.js is used to establish a server for payment process and firebase is storing all the information and data. The functionalities available are order management, product management, rating feature, chat feature, notification, voucher and business insight.